Traffic management algorithms for LEO satellite networks - Huyop @ Ayop, Fahrul Hakim (2016)
Traffic management for Low Earth Orbit (LEO) satellite networks deals with the process of monitoring the network activities by allocating certain traffic into the right path and increasing the throughput rate for the sake of performance and efficiency. This thesis deals with traffic management by improving some algorithms in routing and congestion avoidance to guarantee the subscribers to have their desired QoS. The problem in network arises during the period of coexistence between UDP and FTP traffic in the same network which could affect their performances. The situation is getting worse when the traffic is not equally distributed across the network which could possibly degrade the network performance especially in the case of the delivery of the high priority traffic. A failure to manage traffic classes by routing them according to their type of service could also bring negative impact to LEO satellite network performance. In dealing with traffic routing problem, two algorithms, Dijkstra's Shortest Path and Genetic Algorithm (GA) are combined together and enhanced to re-strategize a better routing mechanism for a heterogeneous mix of traffic classes ranging from traditional voice calls to multimedia data services in Low Earth Orbit (LEO) satellite networks. Those two algorithms are combined together due to the strong possibilities of being unable to achieve the optimal results when implemented separately. Three classes of traffic such as low, medium and high priority are defined and to be allocated to the right path from source to destination with the most privileged is given to the high priority traffic. In satellite network with Multi Protocol Label Switching (MPLS), routing with Extended Dijkstra Shortest Path algorithm is done to improve QoS by minimizing the link shared between UDP and TCP traffic flows. By minimizing the link shared between those traffics, the performance of UDP traffic which carries delay sensitive data could be improved. Since TCP WestwoodNew is designed to be implemented in wired and wireless network environment, there are few drawbacks when TCP WestwoodNew is implemented in the satellite network environment. As an example, the sender cannot fully utilize the available bandwidth because the rate of the congestion window increment in Slow Start phase of TCP WestwoodNew is rather slow. In this thesis, congestion avoidance algorithm of TCP WestwoodNew is enhanced in order to improve the drawbacks. In this thesis, several proposed algorithms have been developed to improve the traffic performance in the LEO satellite network. In order to evaluate the proposed algorithm, a series of experiments to implement Discrete Event Simulation (DES) of a LEO satellite network by using ns-2 and C/C++ are conducted. The performances of the proposed algorithms are then compared with the previously developed algorithms. The important parameters measured in the simulation are delay rate, throughput rate and fair traffic distribution rate. From the results, the proposed algorithms have managed to reduce the average delay rate for the high priority and UDP traffic. The results also indicate that there is an improvement of fair traffic distribution rate in the network where most of the Inter Satellite Links (ISLs) are able to maintain the link loading percentage ranging from 25% to 75%. For the TCP traffic performance, there is 5% improvement in terms of throughput rate increment. Overall, from all the three experiments that have been conducted, the proposed routing algorithms which have been developed to manage the network traffic have proved better than the previously developed algorithms in several perspectives especially for the implementation of real-time applications in LEO satellite networks.